There Is More Than One Way to Do Something Right: Applying Community-Based Approaches to an Archaeology of Banks Island, NWT - Kelvin, Laura Elena (Scholarship@Western, 2016)
This dissertation explores how historical knowledge is produced and maintained within the Inuvialuit (Western Arctic Inuit) community of Sachs Harbour, NWT, to determine how archaeological research can best complement and respect Inuvialuit understandings and ways of knowing the past. When archaeologists apply Indigenous knowledges to their research they often have limited understandings of how these knowledges work, and may apply them inadequately or inappropriately. I employ an archaeological ethnographic approach to help Ikaahukmiut (people with ties to Banks Island, NWT) articulate to archaeologists how they construct their knowledge of Banks Island’s past. Inuvialuit understandings of the past are experiential and holistic in nature and are passed down through oral histories. They are also learned through doing and are embodied and lived in everyday practice. Archaeologists often overlook diversity within the communities with whom they partner in community-based projects. My research aims to recognize diversity in Ikaahukmiut understandings of the past and of archaeology so that it can ultimately be accounted for in developing community-based research. Although sub-communities can be identified based on any social cleavage, I found that participation in sub-communities based on cultural background, family group, generation, and education and employment background had the greatest influences on community understandings of the past and opinions of archaeology. To establish an effective and inclusive community-based archaeology project on Banks Island, archaeologists will need to engage with and navigate diversity within the community. Future projects should be built with two main guiding principles: the Inuvialuit guiding principle of respect and the notion that there is more than one way to do something right. There is a need for future projects to respect traditional beliefs, apply community knowledge, and address community concerns. In general archaeologists establishing community-based projects may need ...